Taxonomic notes on the genus Quwatanabius in Taiwan (Coleoptera: Staphylinidae) - Hu, Fang-Shuo; Bogri, Amalia (Zootaxa, 2020)
The description of the male of the species Quwatanabius chiaw (Smetana, 1995) is provided for the first time, including a habitus photo and illustrations of the aedeagus. A brief discussion of the endemic status of Q. chiaw on the island of Taiwan, as well as additional Taiwanese material of the wide-spread Q. flavicornis (Sharp, 1889) are also provided.